OPTIMALISASI PENGELOLAAN KAWASAN PASAR ULEE KARENG KOTA BANDA ACEH - T. Satria Darma; Teuku Budi Aulia; Safwan Safwan (Prodi Magister Teknik Sipil Unsyiah, 2018)
The purpose of this study is to determine the factors that affect the less optimal management of Ulee Kareng Market, evaluate the role of market managers and provide better solutions to the management of Ulee Kareng Market. This research was using a qualitative method by both observation and interview, and also a quantitative method for the distribution of questionnaires. Numbers of respondents in this research were as many as 163 persons. The statistical analysis used in data processing consists of validity, reliability tests and statistics descriptive. The SPSS software was used to analyze data in this study. The result of factors analysis reveals that causing less optimal management are insufficient in utilizing available parking area, clogged drainage, scattered rubbish and lack of control of street vendors. Furthermore, the Strengths, Weakness, Opportunities, Threats (SWOT) analysis is conducted to explore strategy used in the market. The result from the SWOT analyze suggested for three alternative strategies: 1). Government of Banda Aceh City needs to plan to facilitate the needs of the market in terms of supporting facilities such as drainage, temporary garbage disposal and the traders’ needs of trading activities; 2) strengthen the role and function of market managers in improving services to the needs of traders and buyers in the market area; 3) increase market users awareness to actively participate in keeping, maintaining, and caring for the various facilities that available in the Ulee Kareng Market Area.